Validity of mobile learning-based practicum instructions with a guide inquiry approach to improve critical thinking skills - Windhiana Ayu Lestari; Imas Cintamulya (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
Mobile learning-based practicum instructions to improve critical thinking have not been maximally empowered in schools. This study aims to design mobile learning-based practicum instructions with a guided inquiry approach to enhance critical thinking skills and describe the validity of mobile learning-based practicum instructions with a Guide Inquiry approach to improve critical thinking skills that have been designed. This research uses the Research and Development method with the ADDIE development model. The procedure of this research is analysis, design, and development. This research comes to the stage of product validity. The instrument used in this study is a validity sheet covering aspects of material, systematics, linguistics, and graphics. The data analysis technique used in this study is a quantitative descriptive technique to describe validation data and comment on validator advice. The results of this study show that mobile learning-based practicum instructions have met valid criteria with an average percentage of 84.95%. Thus, it can be concluded that the mobile learning-based practicum instructions with a guided inquiry approach improve critical thinking skills that are designed to be valid.